(untitled) (Research, Society and Development, 2021)
The pandemic caused by COVID-19 affected, on a global scale, the routine of many students. For this group, often affected by mental disorders, social distancing had a greater impact on mental health. The need for social isolation made it impossible to maintain classroom classes, modifying social and eating habits. In this scenario, stress, psychological suffering and irregular sleep act as modifying agents of eating behavior, leading to the adoption of behaviors that are harmful to health, as a compensatory mechanism. However, research aimed at this audience is still scarce, therefore, this study aims to assess the eating behavior of students from federal public education institutions located in the interior of the state of Ceará. Methodology: Research participants answered a self-administered online questionnaire containing questions regarding the consumption of vegetables, fruits, milk and yogurts in the period before and during the pandemic. Results: The findings revealed an increase in the frequency and consumption of vegetables, fruits, milk and yogurts during the period of social distancing. Conclusion: In this study, we can identify an improvement in the students’ eating habits, characterized by an increase in the frequency and consumption of vegetables and fruits, in the form of raw or cooked salads, as well as the consumption of milk and yogurt. This change in dietary patterns may result from the greater availability of time for preparing meals, returning to the family environment and the use of food as an essential tool for strengthening health and the immune system.